Needs Analysis for ESP Course Development: Thai Civil Engineering Students’ Perspectives - Thepseenu, Benjaporn (Asian Journal of Education and Training, 2020)
This study aimed to investigate civil engineering students’ English language learning needs and perceptions of their English for Specific Purposes (ESP) course based on the past students’ perspectives (Brown, 2016). The study sample comprised 85 third-year Thai students, majoring in civil engineering at University of Phayao, Thailand in the academic year 2018. A mixed-methods research design was employed. A questionnaire on civil engineering students’ needs for ESP course was used to investigate the students’ perceived needs on their ESP course. Subsequently, a focus group interview was conducted to explore the students’ overall perceptions of the ESP course they had finished. Data from the questionnaire were analyzed by means of frequency, mean, and standard deviation. Interview data were analyzed using content analysis. The findings revealed students’ high demand of communicative topics particularly speaking and listening in work-related situations. A combination of pair and group work for in-class activities and out-of-class assignments was preferred over working individually. A mixture of Thai and English as a language of instruction was also needed. Pedagogical implications for ESP course designers and teachers of other fields of engineering are put forward to highlight the crucial role of needs analysis in ESP course development.